Etnobotani Familia Zingebaraceae (Suku Jahe-Jahean) di Desa Koto Dua Lama Kecamatan Air Hangat Kabupaten Kerinci - Novinovrita M; Bony Irawan (Symbiotic: Journal of Biological Education and Science, 2020)
Zingiberaceae belongs to the Spermatophyta division, Angiospermae sub division, Liliopsida class, Zingiberidae sub class, Zingiberales order. Zingiberaceae is a plant with habitus in the form of perennial herbs that are aromatic. Zingiberaceae is a basic plant from tropical forests which is found in many shady places and valleys, sometimes also found in secondary forests. In Koto Dua Lama village, many species of Zingiberaceae are found, but have not been inventoried or reported scientifically. This study aims to diversify zingiberacaeae species found in the village of Koto Dua Lama. This type of research is qualitative research. In this study exploratory survey methods were used. The techniques used in collecting data are observation and collection of plants and documentation. In this study 11 species of Zingiberaceae were included in 8 genus and 2 sub-families including Costus speciosus (Sitawa), Alpinia galanga (Lengkueh), Amomum cardomomum (gandan bumbu), Curcuma domestica (kunyit), Curcuma mango (kunyit temu), Curcuma xanthorrhiza (Temulawak), Etlingera elatior (Sabung), Hedychium coronarium (Suli), Kaemferia galanga (Ceku), Zingiber Cassumnar (Kunyit Melai) and Zingiber Officinale (padi-padi). Each type has its own description or characteristics.